GEOMETRIC THINKING LEVEL OF VOCATIONAL HIGH SCHOOL BASED ON VAN HIELE’S THEORY VIEWED FROM GENDER AND MATHEMATICAL ABILITY - Eddy Nugroho; Abadyo Abadyo; Santi Irawati (Jurnal Pendidikan Sains, 2019)
Abstract: The purpose of this study is to describe the level of geometrical thinking of Vocational High School students based on Van Hielle's theory in terms of gender differences. This study used a qualitative approach involving six students of Vocational High School as research subjects consisting of three male students and three female students with different mathematical abilities. The results of this study state that there is no striking difference between the level of geometrical thinking of male and female students who are the subject of research, i.e. all are at the level of thinking one (analysis). Likewise, when viewed from different mathematical abilities, it turns out to be apparent at the level of thinking one, except for one student in the moderate mathematics ability degree who is at the level of zero thinking (visual) because this subject has a low geometry thinking ability. The ideal level of thinking for vocational high school students, the level of thinking two (Abstraction), is not reached. In addition, the lower the level of mathematical ability, the less the indicator is satisfied at the same level of thinking.Key Words: geometrical thinking ability, Van Hiele's theory, gender differenceAbstrak: Tujuan penelitian ini untuk mendeskripsikan tingkat berpikir geometri siswa Sekolah Menengah Kejuruan berdasarkan teori Van Hielle ditinjau dari perbedaan jenis kelamin. Penelitian ini menggunakan pendekatan kualitatif dengan melibatkan enam siswa Sekolah Menengah Kejuruan sebagai subjek penelitian yang terdiri atas tiga siswa putra dan tiga siswa putri dengan kemampuan matematika berbeda. Hasil dari penelitian ini menyatakan bahwa tidak ada perbedaan yang mencolok antara tingkat berpikir geometri siswa putra dan putri yang menjadi subjek penelitian, yaitu semua berada pada tingkat berpikir satu (analisis). Demikian juga jika ditinjau dari kemampuan matematikanya berbeda ternyata semua pada tingkat berpikir satu, kecuali pada seorang siswa kelompok kemampuan matematika sedang yang berada pada tingkat berpikir nol (visual) karena subjek ini memiliki kemampuan berpikir geometri rendah. Tingkat berpikir ideal untuk siswa seusia Sekolah Menengah Kejuruan, yaitu tingkat berpikir dua (Abstraksi) tidak tercapai dan semakin rendah tingkat kemampuan matematikanya semakin berkurang indikator yang terpenuhi pada tingkat berpikir yang sama.Kata kunci: tingkat berpikir geometri, teori Van Hiele, perbedaan jenis kelamin